Assessing the impact of short-term intraocular pressure fluctuations on primary open-angle glaucoma progression - Nina Lutsenko; Taras Nedilka (Ukrainian Society of Ophthalmologists, 2024)
Purpose: To examine the impact of short-term intraocular pressure (IOP) fluctuations on the progression of glaucomatous optic neuropathy based on optical coherence tomography (OCT) data. Material and Methods: Totally, 32 patients (62 eyes) with primary open-angle glaucoma (POAG) were included in the study and divided into two groups. Group 1 comprised 15 patients (30 eyes) with a standard deviation (SD) of IOP of less or equal to 3 mmHg, and group 2, 17 patients (32 eyes) with an SD of IOP greater than 3 mmHg. Patients were followed over 12 months. At baseline, at 6 and 12 months, they had a routine eye examination and OCT of the optic nerve and macula, with retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thicknesses determined. At 12 months, the rebound tonometer ICare Home2 was used for diurnal IOP measurements, and an SD of IOP was determined. Results: In group 1 and group 2, annual losses in RNFL were 3.20 ± 3.86 µm/year and 8.11 ± 9.1 µm/year, respectively (р = 0.03), and global GCC losses, 0.87 ± 3.98% and 5.24 ± 8.05%, respectively (р = 0.04). There was a statistically significant positive correlation of the SD of IOP measurements with annual loss in GCC thickness (r = 0.5161; р = 0.02) and global GCC loss (r = 0.6258; р = 0.03) for group 2, but no significant correlation for group 1. Conclusion: IOP fluctuation (SD > 3 mmHg) is a factor of glaucoma progression which impacts particularly on retinal GCC losses.